Dietary Patterns and Cognitive Decline in Chinese Elderly Singaporeans: A Longitudinal Cohort Study - Veronica Lee; Nazhir Adam (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Cognitive decline is a growing public health concern, especially among aging populations. Diet is a modifiable factor that can influence brain health. This study investigated the longitudinal association between dietary patterns and cognitive decline in Chinese elderly Singaporeans. Methods: A cohort of 1,500 community-dwelling Chinese adults aged ≥60 years in Singapore was followed for 6 years. Dietary intake was assessed at baseline using a validated food frequency questionnaire. Cognitive function was evaluated at baseline and biennially using a comprehensive neuropsychological battery assessing memory, attention, executive function, and language. Dietary patterns were identified using factor analysis. Linear mixed-effects models were used to examine the association between dietary patterns and cognitive trajectories, adjusting for confounders. Results: Three dietary patterns emerged: